Student experiences with learner-generated online discussion forum: active learning as both participants and content creators. (3rd April 2023) - Smith, Deborah B.; Anderson, Billie
This study explored the perceptions and experiences of content creator students enrolled in an undergraduate course in lifespan development. A total of 284 students participated in this study over five semesters. A mixed-methods study design was adopted for data collection, and a thematic analysis of qualitative data was conducted to identify the key themes. The participants identified several themes about why they liked creating content were identified, such as seeing other students' perspectives and autonomy over the learning process, along with several negative aspects of this active learning approach, including having to summarise everyone's responses and unclear directions. These findings can guide other instructors to incorporate active learning online assignments into their existing courses.